Hakikat Evaluasi Dalam Pendidikan Islam - Abdullah Bill Huda; Putri Fadilah Panjaitan; Melani Melani; Dayana Sabila (LPPPI Publishing, 2023)
Evaluating is an activity that aims to understand whether or not the standard goals have been set. This study aims to analyze the nature of evaluation contained in Islamic education. This study uses the library study method, namely by collecting various literature related to evaluation in Islamic education and then analyzing it in order to obtain a conclusion. The results of this study are that evaluation activities are very important to be carried out in Islamic education, because they are so important that evaluation cannot be separated from education itself. Therefore, Islamic education must evaluate based on the duties, functions, and principles that apply to achieving the goals of Islamic education.